(untitled) (Journal of Buffalo Science, 2017)
Thirty farms that raised Lime or Parkote female buffaloes in Kaski were selected for the survey of animal census, feeding traits and body dimensions in the rainy season and the dry season. The average number per farm was 0.76 in Lime and 0.27 in Parkote. The average of age and parity was 8.2 years old and 4.4 in Lime, and 6.6 years old and 2.8 in Parkote, respectively. The mean dry matter (DM) supply of roughage, supplemental feed and total feed was higher in the dry season than in the rainy season (11.8 kg/head/day vs. 10.3 kg/head/day, 1.2 kg/head/day vs. 0.8 kg/head/day, 13.0 kg/head/day vs. 11.1 kg/head/day, respectively, P<0.05). Although the average DM supply of roughage per body weight (BW) and total feed supply per BW had no significant differences between the seasons, the mean DM supply of supplemental feed per BW was higher in the dry season than in the rainy season (0.35% of BW vs. 0.22% of BW, P<0.01). The BW, heart girth (HG) and hip born width (HW) of Parkote were higher than those of Lime (401.7 kg vs. 368.0 kg, 185.7 cm vs. 179.8 cm, 50.4 cm vs. 48.4 cm, respectively, P<0.05). However, the body length, wither height (WH) and criss-cross height showed no significant differences between Lime and Parkote (127.4 cm and 129.8 cm, 118.7 cm and 119.5 cm, 118.0 cm and 119.4 cm, respectively). The BW estimation using body dimensions may play a significant role to know about the buffalo body condition. With the measured BW, HG, WH and HW in this survey, the formulae to estimate BW of Lime and Parkote buffaloes were established.